2014
DOI: 10.1371/journal.pone.0101269
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Insulin Resistance and Adiponectin Signaling in Adipose Tissue by Liver X Receptor Activation Highlights a Cross-Talk with PPARγ

Abstract: Liver X receptors (LXRs) have been recognized as a promising therapeutic target for atherosclerosis; however, their role in insulin sensitivity is controversial. Adiponectin plays a unique role in maintaining insulin sensitivity. Currently, no systematic experiments elucidating the role of LXR activation in insulin function based on adiponectin signaling have been reported. Here, we investigated the role of LXR activation in insulin resistance based on adiponectin signaling, and possible mechanisms. C57BL/6 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
3
17
0
1
Order By: Relevance
“…They have shown that loss of LXR impairs hepatic lipogenesis, accompanied by a reciprocal increase in adipose lipid storage, by promoting adipose PPARγ pathway activity, indicating possible cross-talk between LXR and PPARγ in adipose tissue. Cross-talk between LXR and PPARγ in adipose tissue is also supported by our previous study that showed an antagonising effect of LXR on PPARγ in the regulation of adiponectin expression (Zheng et al 2014).…”
Section: Introductionsupporting
confidence: 66%
“…They have shown that loss of LXR impairs hepatic lipogenesis, accompanied by a reciprocal increase in adipose lipid storage, by promoting adipose PPARγ pathway activity, indicating possible cross-talk between LXR and PPARγ in adipose tissue. Cross-talk between LXR and PPARγ in adipose tissue is also supported by our previous study that showed an antagonising effect of LXR on PPARγ in the regulation of adiponectin expression (Zheng et al 2014).…”
Section: Introductionsupporting
confidence: 66%
“…The differentiated adipocytes experienced increases in mRNA expression levels of SULT1E1, AdipoQ, and PPARγ (Figure 4-14) in comparison to the immortalized human preadipocytes in Figure 4-12. Differentiated adipocytes exhibited overall higher expression of AdipoQ and PPARγ genes and this was consistent with recent literature [250,345,346]. This also holds true for SULT1E1 expression, which was confirmed by the determination of estradiol sulfation in cytosol studies, where SULT1E1 activity was higher in differentiated adipocyte cytosol.…”
Section: -Hr Exposure Of Immortalized Human Adipocytes To Oh-pcbs Fsupporting
confidence: 91%
“…Recently, studies on animal models and cell lines clearly show a cross talk between PPARγ and LXR in the regulation of adipocyte metabolism (8,72,73). This new finding could explain some discrepancies observed in the literature between LXR knockout studies and LXR activation studies in mouse models.…”
Section: Lxr In Lipolysismentioning
confidence: 76%